2014
DOI: 10.1016/j.chembiol.2014.10.013
|View full text |Cite|
|
Sign up to set email alerts
|

The Hedgehog Pathway Effector Smoothened Exhibits Signaling Competency in the Absence of Ciliary Accumulation

Abstract: SUMMARY Misactivation of the seven transmembrane protein Smoothened (Smo) is frequently associated with basal cell carcinoma and medulloblastoma. Cellular exposure to secreted Hedgehog (Hh) protein or oncogenic mutations in Hh pathway components induce Smo accumulation in the primary cilium, an antenna-like organelle with mostly unknown cellular functions. Despite the data supporting an indispensible role of the primary cilium in Smo activation, the mechanistic underpinnings of this dependency remain unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Although ciliary localization of Smo and Gli proteins correlates with Hh pathway activation, definitive proof that ciliary localization of these and other pathway components is required for Hh signal transduction is still lacking. Indeed, a recent study revealed that Smo could activate the Hh signaling pathway in the absence of ciliary accumulation under certain conditions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although ciliary localization of Smo and Gli proteins correlates with Hh pathway activation, definitive proof that ciliary localization of these and other pathway components is required for Hh signal transduction is still lacking. Indeed, a recent study revealed that Smo could activate the Hh signaling pathway in the absence of ciliary accumulation under certain conditions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that Smo‐mediated activation of downstream effectors takes place in an extra‐ciliary location that still awaits identification, and may involve the signaling endosome. When Pik3c2a ‐depleted cells are stimulated with SAG they are able to activate the Hh pathway even in the absence of Smo ciliary accumulation [62]. The fact that PI3K‐C2α exclusively interferes with cilium‐dependent Hh pathway reinforces the hypothesis that the defect seen in Pik3c2a‐ deficient cells is due to impaired trafficking of Smo to cilia.…”
Section: Pi3k‐c2α In Exocytic Trafficmentioning
confidence: 72%
“…A second evidence comes from the use of the synthetic Smo agonist, SAG. SAG stimulation, different from the endogenous ligand Sonic Hedgehog, is able to activate Hh downstream targets without the need of Smo translocation to cilia [62]. It is thought that Smo-mediated activation of downstream effectors takes place in an extra-ciliary location that still awaits identification, and may involve the signaling endosome.…”
Section: Pi3k-c2a In Exocytic Trafficmentioning
confidence: 99%
“…Researchers at the University of Texas Southwestern Medical Center identified a series of small molecule Hh pathway inhibitors from a cell-based screen [39]. Several compounds were identified as potent inhibitors of pathway signaling (IHR-1 – IHR-7) with a range of IC 50 values from 7.6 – 200 nM.…”
Section: Synthetic Small Molecule Smo Antagonistsmentioning
confidence: 99%
“…An acetylated version of IHR-1, IHR-NAc ( 10 ), demonstrated enhanced cellular permeability and was significantly more active against pathway signaling in the presence of SAG (IC 50 = 19 nM). These results strongly suggest that Smo antagonists may not be exhibiting maximum results due to their inability to cross the cell membrane and reach all cellular Smo populations [39]. …”
Section: Synthetic Small Molecule Smo Antagonistsmentioning
confidence: 99%